Robust image communication over wireless channels. - Hemami, S.S (IEEE Communications magazine)
Typical image compression algorithms produce data streams which require a very reliable communication-they are not designed for transmission in an environment in which data may be lost or delayed, as provided by current and next-generation wireless communication networks. Compression and transmission provisions that avoid catastrophic failure caused by lost, delayed, or errant packets are therefore imperative in order to provide reliable visual communication over such systems. This robustness is obtained by modifying the source coding and/or adding channel coding. This article presents an overview of both lossy and lossless source coding techniques and combined source/channel techniques providing robustness, presenting examples of successful techniques